Adhesive film for semiconductor, method for producing adhesive film for semiconductor, adhesive tape for semiconductor, semiconductor device and method for producing semiconductor device
Patent Information
- Application Number
- JP2023134529
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-22
- Publication Date
- 2025-03-07
AI Technical Summary
【0024】 本開示によれば、基材と接する接着剤層の厚みが薄く、かつ、該接着剤層における欠点が少ない接着フィルムを提供することができる。
Smart Images

Figure 2025029740000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an adhesive film for semiconductors, a method for producing an adhesive film for semiconductors, an adhesive tape for semiconductors, a semiconductor device, and a method for producing a semiconductor device. [Background technology]
[0002] Conventionally, wire bonding using thin metal wires such as gold wires has been widely used to connect semiconductor chips and substrates. On the other hand, in order to meet the demands for higher performance, higher integration, higher speed, etc. for semiconductor devices, flip chip connection (FC connection) in which conductive protrusions called bumps are formed on the semiconductor chip or substrate to directly connect the semiconductor chip and substrate is becoming more widespread.
[0003] For example, the COB (Chip On Board) type connection method, which is widely used for BGA (Ball Grid Array), CSP (Chip Size Package), etc., in connection between semiconductor chips and substrates, also corresponds to the FC connection method. The FC connection method is also widely used in the COC (Chip On Chip) type connection method, which forms connection parts (e.g., bumps and wiring) on semiconductor chips to connect between semiconductor chips.
[0004] In addition, for packages that are strongly required to be even smaller, thinner, and more functional, chip-stack packages, POP (Package On Package), TSV (Through-Silicon Via), etc., which stack and multi-layer chips using the above-mentioned connection method, are beginning to become widespread. These stacking and multi-layering technologies arrange semiconductor chips and other components three-dimensionally, making the package smaller than methods that arrange them two-dimensionally. In addition, they are also effective in improving semiconductor performance, reducing noise, reducing mounting area, and saving power, and are therefore attracting attention as the next-generation semiconductor wiring technology.
[0005] Also, from the viewpoint of improving productivity, COW (Chip On Wafer) is attracting attention, in which semiconductor chips are bonded (connected) onto a semiconductor wafer, then separated into individual pieces to create semiconductor packages. From the same viewpoint, gang bonding is also attracting attention, in which multiple semiconductor chips are aligned and temporarily bonded onto a semiconductor wafer or a map substrate, and then these multiple semiconductor chips are bonded together in a final manner to ensure the connection.
[0006] For connecting the above-mentioned connecting members such as semiconductor chips, a film-like adhesive is used (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2018 / 225323 Summary of the Invention [Problem to be solved by the invention]
[0008] In stacking and multi-layering technology for miniaturizing semiconductor packages, thinning of the film adhesive is required. However, thinning of the film adhesive may cause dents, which are called defects, on the surface of the film adhesive. In particular, when a multi-layer film adhesive is used as in Patent Document 1, the thickness of each layer is thin, and the above defects are likely to occur on the surface of the layer that contacts the substrate. Such defects can cause breakage of the semiconductor chip when the semiconductor chip is mounted.
[0009] Therefore, an object of the present disclosure is to provide an adhesive film in which the thickness of the adhesive layer in contact with the substrate is thin and the adhesive layer has few defects. [Means for solving the problem]
[0010] [1] An adhesive film for a semiconductor comprising a substrate and a film-like adhesive in contact with the substrate, The film-like adhesive has an adhesive layer having a thickness of 1 to 10 μm in contact with the base material, The polar component value A of the surface free energy of the surface of the adhesive layer in contact with the substrate 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference from (|A 極性 -B 極性 |) is 8mJ / m 2 The following is an adhesive film for semiconductors.
[0011] [2] The adhesive film for a semiconductor according to [1], wherein the adhesive layer contains an epoxy resin, a curing agent, a thermoplastic resin and an inorganic filler.
[0012] [3] The adhesive film for a semiconductor according to [2], wherein the content of the epoxy resin is 10 to 60 mass % based on the total mass of the adhesive layer.
[0013] [4] The adhesive film for a semiconductor according to any one of [2] and [3], wherein the content of the curing agent is 1 to 40 mass % based on the total mass of the adhesive layer.
[0014] [5] The adhesive film for a semiconductor according to any one of [2] to [4], wherein the thermoplastic resin comprises at least one selected from the group consisting of polyamideimide resins, acrylic resins, polyimide resins, and phenoxy resins.
[0015] [6] The adhesive film for a semiconductor according to any one of [2] to [5], wherein the content of the thermoplastic resin is 5 to 40 mass % based on the total mass of the adhesive layer.
[0016] [7] The adhesive film for a semiconductor according to any one of [2] to [6], wherein the content of the inorganic filler is 30 to 60 mass % based on the total mass of the adhesive layer.
[0017] [8] The adhesive film for a semiconductor according to any one of [1] to [7], wherein the substrate is a polyethylene terephthalate film.
[0018] [9] The surface free energy of the surface of the substrate in contact with the adhesive layer is 10 to 30 mJ / m 2 The adhesive film for a semiconductor according to any one of [1] to [8],
[0019]
[10] The polar component value B 極性 is 0.3 to 5.0 mJ / m 2 The adhesive film for a semiconductor according to any one of [1] to [9],
[0020]
[11] A method for producing an adhesive film for a semiconductor according to any one of [1] to
[10] , A step (A) of preparing the substrate and a coating liquid for forming the adhesive layer; and (B) applying the coating liquid to a surface of the substrate to form the adhesive layer, In the step (A), the polar component value A of the surface free energy of the surface of the adhesive layer in contact with the substrate is 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference from (|A 極性 -B 極性 |) is 8mJ / m 2 The method for producing an adhesive film for a semiconductor includes preparing the substrate and the coating liquid as follows.
[0021]
[12] An adhesive tape for a semiconductor comprising: an adhesive film for a semiconductor according to any one of [1] to
[10] ; and a backgrind tape provided on the adhesive film for a semiconductor on the side opposite to the substrate.
[0022]
[13] A method for producing a semiconductor device using the adhesive film for semiconductor according to any one of [1] to
[10] , A method for manufacturing a semiconductor device, comprising a step of heating and bonding a semiconductor chip and a base body in a state in which the connecting portions of the semiconductor chip and base body face each other via the film adhesive.
[0023]
[14] a semiconductor chip and a base body arranged such that their connection portions face each other; and a sealing portion that bonds the semiconductor chip and the base body and fills a gap between the semiconductor chip and the base body, A semiconductor device, wherein the sealing portion is a cured product of the film-like adhesive in the adhesive film for a semiconductor according to any one of [1] to
[10] . Effect of the Invention
[0024] According to the present disclosure, it is possible to provide an adhesive film in which the thickness of the adhesive layer in contact with the substrate is thin and the adhesive layer has few defects. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a schematic cross-sectional view showing one embodiment of an adhesive film for a semiconductor according to the present disclosure. [Diagram 2] FIG. 2(a) is a schematic cross-sectional view showing one embodiment of a semiconductor device according to the present disclosure, and FIG. 2(b) is a schematic cross-sectional view showing another embodiment of a semiconductor device according to the present disclosure. [Diagram 3] FIG. 3 is a schematic cross-sectional view showing another embodiment of the semiconductor device according to the present disclosure. [Figure 4] 4A to 4C are cross-sectional views illustrating steps in one embodiment of a method for manufacturing a semiconductor device according to the present disclosure. [Diagram 5] 5A to 5C are cross-sectional views illustrating process steps of an embodiment of a method for manufacturing a semiconductor device according to the present disclosure. [Figure 6] 6A to 6C are cross-sectional views illustrating process steps of an embodiment of a method for manufacturing a semiconductor device according to the present disclosure. [Figure 7]7A to 7C are cross-sectional views illustrating process steps of an embodiment of a method for manufacturing a semiconductor device according to the present disclosure. [Figure 8] 8A to 8C are cross-sectional views illustrating steps in one embodiment of a method for manufacturing a semiconductor device according to the present disclosure. [Figure 9] 9A to 9C are cross-sectional views illustrating process steps of one embodiment of a method for manufacturing a semiconductor device according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] In this specification, "(meth)acrylic" means at least one of acrylic and the corresponding methacrylic. The same applies to other similar expressions such as "(meth)acryloyl" and "(meth)acrylate". In addition, a numerical range indicated using "~" indicates a range including the numerical values described before and after "~" as the minimum and maximum values, respectively. In addition, in the numerical range described in this specification, the upper limit or lower limit of the numerical range may be replaced with a value shown in the examples. In addition, the upper limit and lower limit values described individually can be arbitrarily combined. In addition, the materials exemplified below may be used alone or in combination of two or more types, unless otherwise specified. When a plurality of substances corresponding to each component are present in the composition, the content of each component in the composition means the total amount of the plurality of substances present in the composition, unless otherwise specified.
[0027] Hereinafter, exemplary embodiments of the present disclosure will be described. However, the present disclosure is not limited to the following embodiments.
[0028] <Adhesive film for semiconductors and its manufacturing method> One embodiment of the present disclosure is an adhesive film for semiconductors (hereinafter also simply referred to as "adhesive film") that includes a substrate and a film-like adhesive in contact with the substrate. Here, the adhesive film being for semiconductors means that the adhesive film is used to bond a connecting member such as a semiconductor chip to a base and to seal a gap between the connecting member and the base.
[0029] In the adhesive film of the above embodiment, the film-like adhesive has an adhesive layer having a thickness of 1 to 10 μm that contacts the substrate, and the polar component value A of the surface free energy of the surface of the adhesive layer that contacts the substrate 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference from (|A 極性 -B 極性 |) is 8mJ / m 2 The following is the result.
[0030] Here, the polar component value of the surface free energy means the polar term of the solid surface free energy obtained by the Owens and Wendt method, and is calculated using the following Young-Dupre formula (III) from the contact angle between the probe solution and the surface measured using a contact angle meter. By using the following Young-Dupre formula (III), the polar term (polar component value) and the dispersion term (dispersion component value) of the surface free energy can be obtained as a solution to the simultaneous equations. The contact angle is measured with a probe droplet amount of 2.0 μL at a temperature of 20° C., one second after the probe solution is dropped. The measurement is performed 10 times each, and the average value is taken as the contact angle of the measured surface. Two types of probe solutions are used: water and diiodomethane.
[0031]
number
[0032] The adhesive film of the above embodiment has the above difference (|A 極性 -B 極性 |) is 8mJ / m 2 Since the adhesive layer is formed as described below, the adhesive layer tends to have fewer defects. Therefore, according to the adhesive film of the above embodiment, there is a tendency that voids in the resin layer (the film-like adhesive or the sealing portion which is the cured product of the adhesive) are reduced when the semiconductor chip is mounted, and breakage of the semiconductor chip caused by differences in the thermal expansion coefficient can be suppressed.
[0033] Another embodiment of the present disclosure is a method for producing the adhesive film for semiconductor. This method includes a step (A) of preparing a substrate and a coating liquid for forming an adhesive layer, and a step (B) of applying the coating liquid to the surface of the substrate to form an adhesive layer, and in the step (A), a polar component value A of the surface free energy of the surface of the adhesive layer that contacts the substrate is 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference from (|A 極性 -B 極性 |) is 8mJ / m 2 The method is characterized in that a substrate and a coating liquid are prepared as follows.
[0034] According to the manufacturing method of the above embodiment, it is possible to obtain an adhesive film in which the thickness of the adhesive layer in contact with the substrate is thin and the adhesive layer has few defects. The reason why such an effect is obtained is not clear, but it is presumed as follows. That is, it is presumed that the reason why defects occur when the adhesive layer is thin is because the adhesive layer becomes more significantly affected by the substrate surface as a result of the thin adhesive layer. 極性 -B 極性 It is presumed that when |) is small, the compatibility between the adhesive layer and the substrate is good and the adhesive layer is less susceptible to the influence of the substrate surface, thereby suppressing the occurrence of defects during the formation of the adhesive layer and achieving the above-mentioned effects.
[0035] The surface free energy of the adhesive layer (the sum of the polar component value and the dispersive component value of the surface free energy of the surface in contact with the substrate) is the above difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be less than or equal to 10 to 50 mJ / m 2 The surface free energy of the adhesive layer is 15 mJ / m 2 or more than 20mJ / m 2 or more, 45 mJ / m 2 Less than or equal to 40mJ / m 2 It may be the following.
[0036] Polar component value A of the surface free energy of the adhesive layer極性 is the difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be less than or equal to 1 to 20 mJ / m 2 The polar component value A of the surface free energy of the adhesive layer 極性 is 3 mJ / m 2 or more than 5 mJ / m 2 or more, 15 mJ / m 2 Less than or equal to 12mJ / m 2 It may be the following.
[0037] The surface free energy of the substrate (the sum of the polar component value and the dispersive component value of the surface free energy of the surface in contact with the adhesive layer) is the above difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be less than or equal to 10 to 30 mJ / m 2 The surface free energy of the substrate is 15 mJ / m 2 or more than 20mJ / m 2 or more, 20 mJ / m 2 Less than or equal to 15mJ / m 2 It may be the following.
[0038] Polar component value B of the surface free energy of the substrate 極性 is the difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be less than or equal to 0.3 to 5.0 mJ / m 2 The polar component value B of the surface free energy of the substrate 極性 is 0.5 mJ / m 2 More than 1.0mJ / m 2 More than 1.5mJ / m 2 or more than 2.0 mJ / m 2 or more, 5.0 mJ / m 2 Below, 3.0mJ / m 2 Less than or equal to 2.5mJ / m 2 It may be the following.
[0039] Polar component value A of the surface free energy of the adhesive layer 極性 Substantial influencing factors include the type of epoxy resin used as the material, the charge imbalance of the phenoxy resin molecules (the arrangement and amount of O atoms, N atoms, etc.), and the quantitative ratio of the epoxy resin to other components (inorganic filler, hardener, organic filler, photoinitiator, and radical polymerizable compound).
[0040] Factors that substantially influence the dispersion component value of the surface free energy of the adhesive layer include the type of epoxy resin used as the material, the length of the hydrocarbon chain of the phenoxy resin, and the amount of epoxy resin and other components (inorganic filler, curing agent, organic filler, photoinitiator, and radical polymerizable compound).
[0041] Polar component value B of the surface free energy of the substrate 極性 The substantial influencing factor of the polar component value B is the charge imbalance of the molecules on the surface of the substrate (the arrangement and amount of O atoms, N atoms, etc.). Here, the molecules on the surface of the substrate refer to the structure of the surface treatment agent when the substrate is surface-treated with a surface treatment agent. Therefore, the polar component value B 極性 A person skilled in the art can easily adjust the polar component value B by changing the type, amount, treatment method, etc. of the surface treatment agent. In addition, the adhesive strength (tape peel strength) of the surface of the substrate to a polyester adhesive tape can be used as an index to determine the polar component value B 極性 For example, the larger the adhesive force, the larger the polar component value B 極性 The electrostatic state (charge amount) and physical state (surface roughness) of the substrate surface can also be influential factors, but the effects of these are thought to be small.
[0042] The substantial influence factors on the dispersion component value of the surface free energy of the substrate include the length of the hydrocarbon chain of the molecules on the substrate surface.
[0043] The adhesive film and the manufacturing method thereof according to the above embodiment will be described below with reference to the drawings. Note that the film-like adhesive in the adhesive film described below is composed of two layers, but the film-like adhesive may be a single layer or a multi-layer of three or more layers.
[0044] 1 is a schematic cross-sectional view showing one embodiment of an adhesive film for a semiconductor according to the present disclosure. The adhesive film for a semiconductor 1 in FIG.
[0045] (base material) The substrate is, for example, a resin film. Examples of the resin film constituting the substrate include polyolefin films such as polypropylene film and polymethylpentene film, polyester films such as polyethylene terephthalate film and polyethylene naphthalate film, polyimide film, and polyetherimide film.
[0046] The substrate may be a single-layer film made of one type of film, or a multi-layer film made of two or more types of films.
[0047] The substrate has the polar component value B 極性 is 0.3 to 5.0 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be as follows, it is preferable that the substrate is a polyethylene terephthalate film. When the substrate is a multilayer film, it is preferable that the layer closest to the adhesive layer is a layer made of a polyethylene terephthalate film. The thickness of the layer made of a polyethylene terephthalate film may be, for example, 3 to 50 nm.
[0048] The substrate may be a film having a release treatment (e.g., treatment with a surface treatment agent) applied to the surface in contact with the adhesive layer. When the substrate is a multilayer film, the layer closest to the adhesive layer may be a layer made of a film having a release treatment applied to the surface in contact with the adhesive layer (e.g., a polyethylene terephthalate film having a release treatment applied to the surface in contact with the adhesive layer). When the release treatment is treatment with a surface treatment agent, the thickness of the layer made of the surface treatment agent may be, for example, 0.8 to 3.2 nm.
[0049] The arithmetic mean roughness Ra of the surface of the substrate (the surface in contact with the adhesive layer) is, for example, 1 to 50 nm, and may be 2 nm or more or 5 nm or more, and may be 40 nm or less or 30 nm or less. The arithmetic mean roughness Ra is a value measured in accordance with JIS B0601:2013. More specifically, it is measured by the method shown in the examples.
[0050] The thickness of the substrate is preferably from 3 to 50 μm, and more preferably from 10 to 40 μm.
[0051] (Film adhesive) The film-like adhesive 3 has an adhesive layer (first adhesive layer) 4 having a thickness of 1 to 10 μm that contacts the substrate 2, and an adhesive layer (second adhesive layer) 5 that is different from the adhesive layer 4. The boundary between the first adhesive layer 4 and the second adhesive layer 5 is not necessarily clear, and may not be visible. Hereinafter, for convenience, the adhesive that constitutes the first adhesive layer 4 may be referred to as the first adhesive, and the adhesive that constitutes the second adhesive layer 5 may be referred to as the second adhesive.
[0052] [First adhesive layer] The first adhesive layer 4 is made of a first adhesive. The first adhesive may be, for example, a thermosetting composition containing a thermosetting resin and a curing agent for the thermosetting resin, or may be a photo- and thermosetting composition containing a photopolymerizable compound, a photopolymerization initiator, a thermosetting resin, and a curing agent for the thermosetting resin. Here, the term "photopolymerizable compound" refers to a compound that is polymerized by an active species (radical, cation, or anion) generated by a photopolymerization initiator upon irradiation with light (e.g., ultraviolet light), and the term "thermosetting resin" refers to a compound that is cured by a reaction with a curing agent by heat.
[0053] When the first adhesive layer 4 has photocurability, the film-like adhesive 3 can be easily made less fluid by irradiation with light. Specifically, for example, the film-like adhesive 3 can be irradiated with light after being attached to one of the two connecting members (or its precursor), thereby making it possible to reduce the fluidity of the first adhesive layer 4. Therefore, the film-like adhesive 3 can suppress excessive flow of the adhesive when connecting the connecting members together, and can suppress the amount of fillet generation. In addition, when the second adhesive layer 5 of the film-like adhesive 3 does not have photocurability, the film-like adhesive 3 can be attached to one connecting member from the first adhesive layer 4 side (the side opposite to the second adhesive layer 5 side) and then irradiated with light, so that the fluidity of the other connecting member side (i.e., the second adhesive layer 5 side) can be maintained even after light irradiation. Therefore, such a film-like adhesive 3 can ensure sufficient connection reliability.
[0054] In addition, when the first adhesive layer 4 has a thermosetting property in addition to a photosetting property, it can be further cured (thermosetting) by heating while maintaining a suitable fluidity even after photosetting. In this case, even if the adhesive covers the surface of the connection part when the film-like adhesive 3 is attached, the adhesive flows and is removed at the time of connection, so that the cured adhesive is unlikely to remain between the connection parts after connection. The connection reliability can also be improved by designing the first adhesive layer 4 in this way. The fluidity of the adhesive as a whole at the time of connection can be changed by adjusting the smoothness, thickness, composition, light irradiation amount, etc. of the first adhesive layer 4, as well as the thickness, composition, etc. of the second adhesive layer 5. This makes it possible, for example, to reduce the amount of voids generated and ensure good sealing properties (adhesive filling properties).
[0055] Furthermore, when an adhesive with low fluidity is simply used, the gap between the connection parts of the connection members may not be sufficiently filled with the adhesive, which may cause defects such as voids. In the above method, the occurrence of such defects in the film-like adhesive 3 can be reduced by attaching the film-like adhesive 3 to the connection members before reducing the fluidity of the first adhesive layer 4 (i.e., before light irradiation).
[0056] Generally, metal bonding is used to connect connecting members together in order to ensure sufficient connection reliability (e.g., insulation reliability). The main metals used for the connection parts (e.g., bumps and wiring) of connecting members include solder, tin, gold, silver, copper, nickel, etc., and conductive materials containing a plurality of these metals are also used. Impurities may be generated on the surface of the connecting part due to the above-mentioned metals being oxidized to form an oxide film, and impurities such as oxides being attached. If such impurities remain, there is a concern that the connection reliability between the connecting members will decrease, and the merit of adopting the above-mentioned connection method will be lost. Therefore, in order to remove the above-mentioned oxide film and impurities, a flux compound may be contained in the film-like adhesive 3. As described above, when the film-like adhesive 3 is attached to one connecting member from the first adhesive layer 4 side, when the second adhesive layer 5 side is designed to flow on the connecting surface of the other connecting member, it is preferable that the flux compound is contained in the second adhesive layer 5.
[0057] (a) Thermosetting resin Examples of the thermosetting resin include epoxy resin, phenol resin (except when contained as a curing agent), acrylic resin, etc. Among these, epoxy resin is preferably used. The content of the epoxy resin in the thermosetting resin is preferably 80 mass% or more, more preferably 90 mass% or more, based on the total amount of the thermosetting resin. The content of the epoxy resin may be 100 mass% based on the total amount of the thermosetting resin.
[0058] Epoxy resin is a compound having two or more epoxy groups in a molecule. For example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, naphthalene type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, phenol aralkyl type epoxy resin, biphenyl type epoxy resin, triphenylmethane type epoxy resin, triphenolmethane type epoxy resin, dicyclopentadiene type epoxy resin and various polyfunctional epoxy resins can be used as epoxy resins. These can be used alone or as a mixture of two or more kinds. Among these, when a triphenolmethane type epoxy resin (an epoxy resin containing a triphenolmethane skeleton) is used, the amount of fillet generation tends to be further reduced.
[0059] In order to prevent the epoxy resin from decomposing and generating volatile components when connecting at high temperatures, it is preferable to use an epoxy resin whose thermal weight loss rate at 250°C is 5% or less when the temperature at the time of connection is 250°C, and it is preferable to use an epoxy resin whose thermal weight loss rate at 300°C is 5% or less when the temperature at the time of connection is 300°C.
[0060] As the epoxy resin, an epoxy resin that is liquid at 25°C (hereinafter simply referred to as "liquid epoxy resin") may be used from the viewpoint of easily suppressing the occurrence of cracks and fissures on the film surface. Here, "liquid at 25°C" means that the viscosity at 25°C measured with an E-type viscometer is 400 Pa·s or less. Examples of liquid epoxy resins include glycidyl ethers of bisphenol A type, glycidyl ethers of bisphenol AD type, glycidyl ethers of bisphenol S type, glycidyl ethers of bisphenol F type, glycidyl ethers of water-added bisphenol A type, glycidyl ethers of ethylene oxide adducts of bisphenol A type, glycidyl ethers of propylene oxide adducts of bisphenol A type, glycidyl ethers of naphthalene resins, trifunctional or tetrafunctional glycidyl amines, and the like.
[0061] The content of the liquid epoxy resin in the thermosetting resin is preferably 5% by mass or more, more preferably 10% by mass or more, and even more preferably 20% by mass or more, based on the total amount of the thermosetting resin, from the viewpoint of easily suppressing the occurrence of cracks and fissures on the film surface. The content of the liquid epoxy resin is preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less, based on the total amount of the thermosetting resin, from the viewpoint of easily suppressing the excessive increase in tackiness of the film and from the viewpoint of easily suppressing edge fusion.
[0062] The reactive functional group equivalent of the thermosetting resin (for example, the epoxy equivalent of the epoxy resin) may be 100 to 3000 g / eq, or may be 100 to 2000 g / eq, or 100 to 1500 g / eq. When the reactive functional group equivalent is within the above range, the balance between reactivity and fluidity during heating tends to be good.
[0063] The content of the epoxy resin in the first adhesive layer 4 is determined from the viewpoint of easily suppressing the occurrence of fillets and from the viewpoint of the polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of easily achieving the above-mentioned polar component value A, the content of the epoxy resin in the first adhesive layer 4 is preferably 10 mass % or more, more preferably 25 mass % or more, further preferably 30 mass % or more, and particularly preferably 35 mass % or more, based on the total mass of the first adhesive layer 4. The content of the epoxy resin in the first adhesive layer 4 is determined from the viewpoint of easily achieving good sealing properties, easily suppressing the occurrence of voids, and easily achieving the above-mentioned polar component value A. 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of what tends to be the above, the content of the epoxy resin in the first adhesive layer 4 is preferably 60 mass % or less, more preferably 50 mass % or less, further preferably 45 mass % or less, and particularly preferably 40 mass % or less, based on the total mass of the first adhesive layer 4. From these viewpoints, the content of the epoxy resin in the first adhesive layer 4 is preferably 10 to 60 mass %.
[0064] The range of the content of the thermosetting resin in the first adhesive layer 4 may be the same as the range exemplified above as the content of the epoxy resin.
[0065] When the first adhesive layer 4 contains a photopolymerizable compound, the content of the epoxy resin and the content of the thermosetting resin may be set in relation to the content of the photopolymerizable compound. The ratio of the content of the epoxy resin (or the content of the thermosetting resin) to the content of the photopolymerizable compound in the first adhesive layer 4 may be 3 to 11 in mass ratio. In this case, high connection reliability is easily obtained, and the occurrence of fillets tends to be further reduced. The above ratio may be 5 or more, 7 or more, or 9 or more from the viewpoint of further reducing the occurrence of fillets, and may be 10 or less from the viewpoint of easily obtaining good sealing properties and easily suppressing the occurrence of defects in addition to the above effect.
[0066] (b) Hardener As the curing agent, a known curing agent known as a curing agent for thermosetting resins can be used. The curing agent also includes materials generally known as curing accelerators. When an epoxy resin is used as the thermosetting resin, the curing agent can be, for example, a phenolic resin-based curing agent, an acid anhydride-based curing agent, an amine-based curing agent, an imidazole-based curing agent, a phosphine-based curing agent, or the like. Among these, the phenolic resin-based curing agent, the acid anhydride-based curing agent, the amine-based curing agent, and the imidazole-based curing agent exhibit flux activity that suppresses the generation of an oxide film at the connection portion, so that the connection reliability can be improved by using these curing agents. From the viewpoint of being able to rapidly proceed with curing when heating is performed at a low temperature, it is preferable to use an imidazole-based curing agent.
[0067] Examples of the imidazole-based curing agent include 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyano-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine, and 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine. -[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, and adducts of epoxy resin and imidazoles. In addition, latent curing agents in which these are microencapsulated can also be used. These can be used alone or in combination of two or more. Among these, compounds having a triazine ring are preferably used from the viewpoint of obtaining better sealing properties and suppressing the occurrence of voids.
[0068] The content of the curing agent in the first adhesive layer 4 is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, relative to 100 parts by mass of the thermosetting resin, from the viewpoint of improving the curing property when heated. The content of the curing agent in the first adhesive layer 4 is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the thermosetting resin, from the viewpoint of making it more difficult for the first adhesive to be interposed between the connecting parts.
[0069] The content of the curing agent in the first adhesive layer 4 is the above polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A極性 -B 極性 |) is 8mJ / m 2 From the viewpoint that the content of the curing agent in the first adhesive layer 4 is likely to be 1 to 40 mass % based on the total mass of the first adhesive layer 4. From the similar viewpoint, the content of the curing agent in the first adhesive layer 4 may be 2 mass % or more, 5 mass % or less, or 4 mass % or less based on the total mass of the first adhesive layer 4.
[0070] (c) Photopolymerizable compound The photopolymerizable compound may be a radical polymerizable compound, a cationic polymerizable compound, or an anionic polymerizable compound. The polymerizability of the photopolymerizable compound may be selected in relation to the curability of the thermosetting resin and the curing agent so as not to inhibit the reaction of the thermosetting resin and the curing agent. For example, when the thermosetting resin has cationic curability or anionic curability, it is preferable to use a radical polymerizable compound as the photopolymerizable compound.
[0071] From the viewpoint of reaction rate, the photopolymerizable compound is preferably a radical polymerizable compound. In this case, a photoradical polymerization initiator is used as the photopolymerization initiator.
[0072] Examples of the radical polymerizable compound include (meth)acrylic compounds and vinyl compounds. As the radical polymerizable compound, (meth)acrylic compounds are preferred from the viewpoint of excellent durability, electrical insulation and heat resistance. The (meth)acrylic compound may be a compound having one or more (meth)acryloyl groups in the molecule. Examples of the (meth)acrylic compound include (meth)acrylic compounds containing a skeleton of bisphenol A type, bisphenol F type, naphthalene type, phenol novolac type, cresol novolac type, phenol aralkyl type, biphenyl type, triphenylmethane type, dicyclopentadiene type, fluorene type, adamantane type or isocyanuric acid type; various polyfunctional (meth)acrylic compounds (excluding (meth)acrylic compounds containing the skeleton) and the like. Examples of polyfunctional (meth)acrylic compounds include pentaerythritol tri(meth)acrylate, dipentaerythritol poly(meth)acrylate (dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc.), and trimethylolpropane di(meth)acrylate. Among these, polyfunctional (meth)acrylic compounds are preferred, and dipentaerythritol poly(meth)acrylate is more preferred. The number of functional groups (the number of (meth)acryloyl groups) of the polyfunctional (meth)acrylic compound is preferably 2 to 8, more preferably 3 to 7, and even more preferably 4 to 6.
[0073] The molecular weight of the photopolymerizable compound is, for example, 400 to 2000. The molecular weight of the photopolymerizable compound is preferably smaller than 2000, and more preferably equal to or less than 1000. The smaller the molecular weight of the photopolymerizable compound, the easier the reaction proceeds and the higher the curing reaction rate.
[0074] The photopolymerizable compounds may be used alone or in combination of two or more.
[0075] From the viewpoint of further reducing the occurrence of fillets, the content of the photopolymerizable compound in the first adhesive layer 4 is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more, based on the total mass of the first adhesive layer 4. From the viewpoint of improving sealing property and suppressing the occurrence of voids, the content of the photopolymerizable compound in the first adhesive layer 4 is preferably 10% by mass or less, more preferably 7% by mass or less, and even more preferably 5% by mass or less, based on the total mass of the first adhesive layer 4. From these viewpoints, the content of the photopolymerizable compound in the first adhesive layer 4 is preferably 1 to 10% by mass, more preferably 3 to 7% by mass, and even more preferably 3 to 5% by mass, based on the total mass of the first adhesive layer 4.
[0076] (d) Photopolymerization initiator The photopolymerization initiator may be a photoradical polymerization initiator, a cationic polymerization initiator, or an anionic polymerization initiator. The photopolymerization initiator can be selected depending on the type of the photopolymerizable compound, and a photoradical polymerization initiator is preferably used for the same reasons as those for the photopolymerizable compound.
[0077] The photoradical polymerization initiator is a compound that decomposes and generates free radicals when irradiated with light having a wavelength in the range of, for example, 150 to 750 nm, preferably light having a wavelength in the range of 254 to 405 nm, more preferably light having a wavelength of 365 nm (e.g., ultraviolet light). As the photoradical polymerization initiator, one type of compound may be used alone, or multiple types of compounds may be used in combination.
[0078] Examples of the photoradical polymerization initiator include photopolymerization initiators having an oxime ester structure, a bisimidazole structure, an acridine structure, an α-aminoalkylphenone structure, an aminobenzophenone structure, an N-phenylglycine structure, an acylphosphine oxide structure, a benzyl dimethyl ketal structure, an α-hydroxyalkylphenone structure, an α-hydroxyacetophenone structure, etc. Among these, from the viewpoint of reactivity and the viewpoint of easier reduction in the amount of fillet generation, it is preferable to use a compound having at least one structure selected from the group consisting of an acylphosphine oxide structure, an α-hydroxyalkylphenone structure, and an α-hydroxyacetophenone structure, it is more preferable to use a compound having at least one structure selected from the group consisting of an acylphosphine oxide structure and an α-hydroxyacetophenone structure, and it is even more preferable to use a compound having an acylphosphine oxide structure.
[0079] Specific examples of the compound having an acylphosphine oxide structure include bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2,4,6-trimethylbenzoyl-diphenyl-phosphine oxide.
[0080] A specific example of a compound having an α-hydroxyalkylphenone structure is 1-hydroxycyclohexyl phenyl ketone.
[0081] Specific examples of compounds having an α-hydroxyacetophenone structure include 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one.
[0082] Among the above, it is preferable to use at least one compound selected from the group consisting of 1-hydroxycyclohexyl phenyl ketone, phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, it is more preferable to use at least one compound selected from the group consisting of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, and it is even more preferable to use phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide.
[0083] The molecular weight of the photoradical polymerization initiator is preferably 400 or more (for example, 300 to 600) from the viewpoint of suppressing volatilization due to heat during film formation, attachment, and the like.
[0084] The content of the photoradical polymerization initiator in the first adhesive layer 4 is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, and even more preferably 1 part by mass or more, relative to 100 parts by mass of the photopolymerizable compound, from the viewpoint of easily progressing the curing sufficiently. The content of the photoradical polymerization initiator in the first adhesive layer 4 is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1.5 parts by mass or less, relative to 100 parts by mass of the photopolymerizable compound, from the viewpoint of suppressing the shortening of the molecular chain due to the rapid progress of the curing reaction and the remaining of unreacted groups. From these viewpoints, the content of the photoradical polymerization initiator in the first adhesive layer 4 is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 3 parts by mass, and even more preferably 0.5 to 1.5 parts by mass, relative to 100 parts by mass of the photopolymerizable compound.
[0085] (e) Other ingredients The first adhesive layer 4 has the polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性|) is 8mJ / m 2 From the viewpoint of the following tendency, it is preferable that the first adhesive layer 4 contains a thermoplastic resin and an inorganic filler, and it is more preferable that the first adhesive layer 4 contains an epoxy resin, a curing agent (a curing agent for an epoxy resin), a thermoplastic resin, and an inorganic filler. The first adhesive layer 4 may contain an organic filler. Hereinafter, the organic filler and the inorganic filler are collectively referred to as a filler.
[0086] The thermoplastic resin contributes to improving heat resistance and film formability. Examples of the thermoplastic resin include polyamideimide resin, acrylic resin, polyimide resin, phenoxy resin, polyamide resin, polycarbodiimide resin, cyanate ester resin, polyester resin, polyethylene resin, polyethersulfone resin, polyetherimide resin, polyvinyl acetal resin, urethane resin, and acrylic rubber. Among these, the above polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of being likely to be as follows, it is preferable to use at least one selected from the group consisting of polyamide-imide resin, acrylic resin, polyimide resin, and phenoxy resin. One type of thermoplastic resin may be used alone, or a mixture or copolymer of two or more types may be used.
[0087] The weight average molecular weight of the thermoplastic resin is, for example, 10,000 or more, and may be 20,000 or more, or 30,000 or more. Such a thermoplastic resin can further improve the heat resistance and film formability of the first adhesive. The weight average molecular weight of the thermoplastic resin may be 1,000,000 or less, or may be 500,000 or less, from the viewpoint of easily obtaining an improved effect in heat resistance. In this specification, the weight average molecular weight means the weight average molecular weight measured in terms of polystyrene using high performance liquid chromatography (manufactured by Shimadzu Corporation, product name: C-R4A). For the measurement, for example, the following conditions can be used. Detector: LV4000 UV Detector (product name, manufactured by Hitachi, Ltd.) Pump: L6000 Pump (product name, manufactured by Hitachi, Ltd.) Column: Gelpack GL-S300MDT-5 (total of 2) (manufactured by Resonac Co., Ltd., product name) Eluent: THF / DMF=1 / 1 (volume ratio) + LiBr (0.03mol / L) + H3PO4 (0.06mol / L) Flow rate: 1mL / min
[0088] From the viewpoint of excellent adhesion of the film-like adhesive 3 to a connecting member (e.g., a semiconductor chip), the glass transition temperature (Tg) of the thermoplastic resin is preferably 120° C. or less, more preferably 100° C. or less, and even more preferably 85° C. or less. The above Tg is the Tg measured using a DSC (manufactured by PerkinElmer, product name: DSC-7) under the conditions of a sample amount of 10 mg, a heating rate of 10° C. / min, and a measurement atmosphere of air.
[0089] The content of the thermoplastic resin in the first adhesive layer 4 is determined from the viewpoint of improving the heat resistance and film formability of the adhesive and from the viewpoint of the difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of easily suppressing the occurrence of fillets and from the viewpoint of preventing the above difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint that the content of the thermoplastic resin in the first adhesive layer 4 is likely to be 40 mass % or less, more preferably 30 mass % or less, further preferably 25 mass % or less, and particularly preferably 20 mass % or less, based on the total mass of the first adhesive layer 4. From these viewpoints, the content of the thermoplastic resin in the first adhesive layer 4 is preferably 5 to 40 mass % based on the total mass of the first adhesive layer 4.
[0090] The filler is effective in controlling the viscosity of the first adhesive, the physical properties of the cured product of the first adhesive, and the like. Specifically, by using the filler, it is possible to suppress the generation of voids during connection, reduce the moisture absorption rate of the cured product of the first adhesive, and the like. The filler may be an inorganic filler (inorganic particles) or an organic filler (organic particles). Examples of the inorganic filler include insulating inorganic fillers such as glass, silica, alumina, titanium oxide, mica, and boron nitride. Among these, it is preferable to use at least one selected from the group consisting of silica, alumina, titanium oxide, and boron nitride, and it is more preferable to use at least one selected from the group consisting of silica, alumina, and boron nitride. Examples of the organic filler include resin fillers (resin particles). Examples of the resin filler include polyurethane and polyimide. The resin filler can impart flexibility at high temperatures such as 260°C. Note that an organic filler made of a thermoplastic resin is not considered to be the above-mentioned thermoplastic resin.
[0091] From the viewpoint of achieving even better insulation reliability, the filler is preferably insulating. The first adhesive layer 4 preferably does not contain a filler (conductive filler) containing a conductive material such as silver, solder, or carbon black.
[0092] The physical properties of the filler may be appropriately adjusted by surface treatment. The filler may be a filler that has been surface-treated from the viewpoint of improving dispersibility or adhesive strength. Examples of the surface treatment agent include glycidyl-based (epoxy-based), amine-based, phenyl-based, phenylamino-based, (meth)acrylic-based, and vinyl-based compounds.
[0093] The average particle size of the filler is, for example, 0.5 to 1.5 μm. From the viewpoint of preventing jamming during flip chip connection, the average particle size of the filler is preferably 1.5 μm or less, and from the viewpoint of excellent visibility (transparency), it is more preferably 1.0 μm or less. The average particle size of the filler is the particle size at the point corresponding to 50% volume when a cumulative frequency distribution curve of particle sizes is calculated assuming the total volume of the particles to be 100%, and can be measured by a particle size distribution measuring device using a laser diffraction scattering method, or the like.
[0094] The content of the inorganic filler in the first adhesive layer 4 is determined from the viewpoint of suppressing a decrease in heat dissipation, the viewpoint of easily suppressing the occurrence of voids and an increase in moisture absorption rate, and the viewpoint of suppressing the polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint of easily achieving the above-mentioned polar component value A, the content of the inorganic filler in the first adhesive layer 4 is more preferably 30% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the first adhesive layer 4. The content of the inorganic filler in the first adhesive layer 4 is set to 30% by mass or more, based on the total mass of the first adhesive layer 4, from the viewpoint of preventing the filler from being trapped in the connection portion and from the viewpoint of achieving the above-mentioned polar component value A 極性 is 1 to 20 mJ / m 2 The difference (|A 極性 -B 極性 |) is 8mJ / m 2 From the viewpoint that the content of the inorganic filler in the first adhesive layer 4 is likely to be 60 mass % or less, more preferably 55 mass % or less, and even more preferably 50 mass % or less, based on the total mass of the first adhesive layer 4. From these viewpoints, the content of the inorganic filler in the first adhesive layer 4 is preferably 30 to 60 mass % based on the total mass of the first adhesive layer 4.
[0095] When the first adhesive layer 4 contains an inorganic filler and an organic filler, the content of the inorganic filler in the first adhesive layer 4 may be 60 mass% or more, 70 mass% or more, or 80 mass% or more, and may be 98 mass% or less, 95 mass% or less, or 90 mass% or less, or may be 60 to 98 mass%, 70 to 95 mass%, or 80 to 90 mass%, based on the total mass of the filler in the first adhesive layer 4.
[0096] The content of the filler in the first adhesive layer 4 is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the first adhesive layer 4, from the viewpoint of suppressing a decrease in heat dissipation and of easily suppressing the occurrence of voids, an increase in moisture absorption rate, etc. The content of the filler is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total mass of the first adhesive layer 4, from the viewpoint of suppressing the occurrence of biting (trapping) of the filler in the connection parts.
[0097] The first adhesive layer 4 may further contain additives such as an antioxidant, a silane coupling agent, a titanium coupling agent, a leveling agent, and an ion trapping agent. These may be used alone or in combination of two or more. The content of these may be appropriately adjusted so that the effect of each additive is exerted. The first adhesive layer 4 may contain a flux compound described later, but the content of the flux compound is preferably less than 0.5 mass%, more preferably less than 0.01 mass%, and even more preferably 0 mass%, based on the total mass of the first adhesive layer 4. In particular, when the first adhesive layer 4 has radical polymerizability (radical curability), the curing of the first adhesive layer 4 is easily inhibited by the flux compound, so it is preferable that the first adhesive layer 4 does not contain a flux compound.
[0098] The thickness of the first adhesive layer 4 (the length in the thickness direction of the film-shaped adhesive 3) may be appropriately set in relation to the height of the connection part in the connection member to which the film-shaped adhesive 3 is attached. Assuming the height of the connection part is y1 and the thickness of the first adhesive layer 4 is x1, from the perspective that it is difficult for the cured product of the first adhesive to intervene between the connection parts and the connection reliability can be further improved, it is preferable that x1 < y1, and more preferably 1.0x1 < y1 ≦ 1.5x1. Specifically, the thickness of the first adhesive layer 4 may be 1 to 50 μm, or may be 3 to 50 μm, 4 to 30 μm, or 5 to 20 μm.
[0099] [Second Adhesive Layer] The second adhesive layer 5 is made of a second adhesive. The second adhesive is, for example, a thermosetting composition containing a thermosetting resin, a curing agent, and a flux compound.
[0100] As the thermosetting resin and the curing agent, the same ones as those exemplified as the thermosetting resin and the curing agent contained in the first adhesive layer 4 can be used. The preferred examples of the thermosetting resin and the curing agent are also the same as those in the case of the first adhesive layer 4. The thermosetting resin and the curing agent in the first adhesive layer 4 and the thermosetting resin and the curing agent in the second adhesive layer 5 may be the same or different.
[0101] From the perspective of easily suppressing the generation of fillets, the content of the thermosetting resin in the second adhesive layer 5 is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more based on the total mass of the second adhesive layer 5. From the perspective of easily obtaining good sealing properties and adhesiveness, the content of the thermosetting resin is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less based on the total mass of the second adhesive layer 5.
[0102] The content of the curing agent in the second adhesive layer 5 is preferably 1 part by mass or more, more preferably 2 parts by mass or more, and even more preferably 3 parts by mass or more, relative to 100 parts by mass of the thermosetting resin, from the viewpoint of improving the curing property when heated. The content of the curing agent is preferably 10 parts by mass or less, more preferably 7 parts by mass or less, and even more preferably 5 parts by mass or less, relative to 100 parts by mass of the thermosetting resin, from the viewpoint of making it more difficult for the second adhesive to be interposed between the connecting parts. The above-mentioned thermosetting resin is the thermosetting resin in the second adhesive layer 5.
[0103] [Flux compounds] The flux compound is a compound having flux activity. As the flux compound, any known compound can be used without particular limitation as long as it can reduce and remove the oxide film on the surface of the solder or the like to facilitate metal bonding. The flux compound may be used alone or in combination of two or more kinds.
[0104] From the viewpoint of obtaining sufficient flux activity and obtaining better connection reliability, the flux compound preferably has a carboxy group, more preferably has two or more carboxy groups, and even more preferably has two carboxy groups. A compound having two or more carboxy groups is less likely to volatilize due to high temperatures during connection compared to a compound having one carboxy group (monocarboxylic acid). Therefore, the compound can further suppress the generation of voids. In addition, a compound having two carboxy groups is more effective at suppressing the increase in viscosity of the film-like adhesive 3 during storage, connection work, etc., compared to a compound having three or more carboxy groups.
[0105] As the flux compound having a carboxy group, a compound having a group represented by the following formula (1) is preferably used.
[0106] [ka]
[0107] In formula (1), R 1represents a hydrogen atom or an electron-donating group.
[0108] From the viewpoint of excellent reflow resistance and even better connection reliability, R 1 In this embodiment, the second adhesive layer 5 contains an epoxy resin, and further contains, among the compounds having a group represented by formula (1), R 1 is an electron donating group. In this case, even in the flip chip connection method, it becomes easy to manufacture a semiconductor device having excellent reflow resistance and connection reliability.
[0109] Examples of the electron-donating group include an alkyl group, a hydroxyl group, an amino group, an alkoxy group, an alkylamino group, etc. As the electron-donating group, a group that is less reactive with other components (e.g., an epoxy resin) is preferable, and specifically, an alkyl group, a hydroxyl group, or an alkoxy group is preferable, and an alkyl group is more preferable.
[0110] The alkyl group may be linear or branched, but is preferably linear. The alkyl group is preferably an alkyl group having 1 to 10 carbon atoms, more preferably an alkyl group having 1 to 5 carbon atoms. The greater the carbon number of the alkyl group, the greater the electron donating property and steric hindrance tend to be. An alkyl group having a carbon number within the above range has an excellent balance between electron donating property and steric hindrance.
[0111] As a flux compound having two carboxy groups, a compound represented by the following formula (2) can be suitably used. The compound represented by the following formula (2) can further improve the reflow resistance and connection reliability of a semiconductor device.
[0112] [ka]
[0113] In formula (2), R 1 is the same as formula (1). 2represents a hydrogen atom or an electron-donating group, and n represents an integer of 0 or 1 or more.
[0114] R 2 The electron donating property indicated by R 1 The examples of the electron donating group are the same as those described above. 2 is R 1 may be the same as or different from each other. 2 may be the same or different from each other.
[0115] In formula (2), n is preferably 1 or more. When n is 1 or more, the flux compound is less likely to volatilize even at high temperatures during connection, and the generation of voids can be further suppressed, compared with the case where n is 0. Furthermore, in formula (2), n is preferably 15 or less, more preferably 11 or less, and may be 6 or less or 4 or less. When n is 15 or less, even better connection reliability can be obtained.
[0116] Specific examples of the flux compound include dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, and dodecanedioic acid, as well as compounds in which an electron-donating group is substituted at the 2-position of these dicarboxylic acids (e.g., 2-methylglutaric acid).
[0117] The melting point of the flux compound is preferably 150°C or less, more preferably 140°C or less, and even more preferably 130°C or less. Such a flux compound is likely to fully exhibit flux activity before the curing reaction between the epoxy resin and the curing agent occurs. Therefore, by using such a flux compound, a semiconductor device with even better connection reliability can be obtained. The flux compound is preferably solid at room temperature (25°C). The melting point of the flux compound is preferably 25°C or more, more preferably 50°C or more. In this specification, a melting point of 150°C or less means that the upper limit of the melting point is 150°C or less, and a melting point of 25°C or more means that the lower limit of the melting point is 25°C or more.
[0118] From the viewpoint of obtaining a better flux effect, the content of the flux compound in the second adhesive layer 5 is preferably 0.1 mass % or more, more preferably 0.3 mass % or more, and even more preferably 0.5 mass % or more, based on the total mass of the second adhesive layer 5. From the viewpoint of reducing the amount of warping of a wafer during the manufacture of a semiconductor device, the content of the flux compound is preferably 5 mass % or less, more preferably 3 mass % or less, and even more preferably 2 mass % or less, based on the total mass of the second adhesive layer 5.
[0119] The second adhesive layer 5 may further contain a filler, a thermoplastic resin, etc., similarly to the first adhesive layer 4. The same ones exemplified as those that may be contained in the first adhesive layer 4 can be used. The preferred examples of these are also the same as those in the first adhesive layer 4. The filler in the first adhesive layer 4 and the filler in the second adhesive layer 5 may be the same or different. The same applies to the thermoplastic resin.
[0120] From the viewpoint of easily improving the heat resistance and film formability of the adhesive, the content of the thermoplastic resin in the second adhesive layer 5 is preferably 5% by mass or more, more preferably 7% by mass or more, and even more preferably 10% by mass or more, based on the total mass of the second adhesive layer 5. From the viewpoint of easily suppressing the occurrence of fillets, the content of the thermoplastic resin is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on the total mass of the second adhesive layer 5.
[0121] The content of the filler in the second adhesive layer 5 is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the second adhesive layer 5, from the viewpoint of suppressing a decrease in heat dissipation and of easily suppressing the occurrence of voids, an increase in moisture absorption rate, etc. The content of the filler is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total mass of the second adhesive layer 5, from the viewpoint of suppressing the occurrence of biting (trapping) of the filler in the connection portion.
[0122] The second adhesive layer 5 may further contain the additives exemplified as the additives that may be contained in the first adhesive layer 4. The contents of these additives may be appropriately adjusted so that the effects of each additive are exerted.
[0123] The second adhesive layer 5 may not contain a combination of a photopolymerizable compound and a photopolymerization initiator. When a photopolymerization initiator is not used, the second adhesive layer 5 may contain a compound that can be contained in the first adhesive layer 4 as a photopolymerizable compound. However, from the viewpoint of preventing a reaction with the active species generated when the first adhesive layer 4 is cured, it is preferable that the second adhesive layer 5 does not contain a compound that is polymerized by the active species generated by the photopolymerization initiator contained in the first adhesive layer 4. The content of the compound that is polymerized by the active species generated by the photopolymerization initiator is preferably 0.5% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0% by mass, based on the total mass of the second adhesive layer 5.
[0124] As described above, some flux compounds deactivate radicals, and the presence of a radical polymerizable compound causes a curing reaction to proceed rapidly upon heating, making it easier for the cured product of the second adhesive to intervene between the connecting parts, so it is preferable that the second adhesive layer 5 does not contain a radical polymerizable compound. The content of the radical polymerizable compound is preferably 0.5 mass% or less, more preferably 0.05 mass% or less, and even more preferably 0 mass%, based on the total mass of the second adhesive layer 5.
[0125] The thickness of the second adhesive layer 5 (the length in the thickness direction of the film-like adhesive 3) may be 1 to 50 μm, or may be 3 to 50 μm, 4 to 30 μm, or 5 to 20 μm.
[0126] The thickness of the second adhesive layer 5 may be 0.5 to 2 times, or 0.5 to 2.5 times, or 0.5 to 3 times, the thickness of the first adhesive layer 4 .
[0127] The thickness of the film-like adhesive 3 (for example, the sum of the thickness of the first adhesive layer 4 and the thickness of the second adhesive layer 5) may be appropriately set in relation to the connection part of the connection member. When the sum of the heights of the connection parts is x and the total thickness of the film-like adhesive is y, the relationship between x and y preferably satisfies 0.70x≦y≦1.3x, and more preferably satisfies 0.80x≦y≦1.2x, from the viewpoint of the connectivity during pressure bonding and the filling property of the adhesive. From the viewpoint of making it difficult for the cured product of the first adhesive to intervene between the connection parts and further improving the connection reliability, it is preferable to satisfy y>x. Specifically, the thickness of the film-like adhesive 3 may be 2 to 100 μm, or may be 6 to 100 μm, 8 to 60 μm, or 10 to 40 μm.
[0128] The manufacturing method of the above adhesive film 1 includes a step (A) of preparing a substrate 2, a coating liquid for forming a first adhesive layer 4, and a coating liquid for forming a second adhesive layer 5, a step (B) of applying the coating liquid to the surface of the substrate 2 to form the first adhesive layer 4, and a step (C) of providing the second adhesive layer 5 on the first adhesive layer 4.
[0129] In step (A), the polar component value A 極性 Influence factor of polar component value B 極性 Taking into account the influencing factors of 極性 -B 極性 |) is 8mJ / m 2 A substrate and a coating liquid are prepared as follows. The coating liquid for forming the first adhesive layer 4 is obtained, for example, by adding the materials for the first adhesive layer 4 (a photopolymerizable compound, a photopolymerization initiator, a thermosetting resin, a curing agent, etc.) to an organic solvent and dissolving or dispersing them by stirring, mixing, kneading, etc. The same applies to the coating liquid for forming the second adhesive layer 5.
[0130] The organic solvent used in preparing the coating liquid is preferably one that has the property of uniformly dissolving or dispersing each component, and examples thereof include dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone, dimethylsulfoxide, diethylene glycol dimethyl ether, toluene, benzene, xylene, methyl ethyl ketone, tetrahydrofuran, ethyl cellosolve, ethyl cellosolve acetate, butyl cellosolve, dioxane, cyclohexanone, and ethyl acetate. These organic solvents can be used alone or in combination of two or more. The stirring, mixing, and kneading in preparing the coating liquid can be performed using, for example, a stirrer, a grinding machine, a three-roll mill, a ball mill, a bead mill, or a homodisper.
[0131] In step (B), the coating liquid is applied onto the substrate 2 using a knife coater, a roll coater, an applicator, or the like to form a coating film, and then the coating film is heated to reduce the organic solvent therein, thereby forming a first adhesive layer 4.
[0132] The drying conditions for volatilizing the organic solvent from the coating film on the substrate 2 are preferably conditions that allow the organic solvent to volatilize sufficiently, and specifically, heating is preferably performed at 50 to 200° C. for 0.1 to 90 minutes. If there is no effect on voids or viscosity adjustment after mounting, the organic solvent is preferably removed to 1.5 mass % or less with respect to the total amount of the first adhesive.
[0133] In step (C), similarly to step (B), a coating liquid for forming the second adhesive layer 5 is applied onto the substrate, and the second adhesive layer 5 is formed by drying the coating liquid, and then the first adhesive layer 4 and the second adhesive layer 5 film are laminated together to provide the second adhesive layer 5 on the first adhesive layer 4. Examples of a method for laminating the first adhesive layer 4 and the second adhesive layer 5 film include methods such as hot pressing, roll lamination, and vacuum lamination. The lamination may be performed, for example, under heating conditions of 30 to 120°C.
[0134] In step (C), similarly to step (B), a coating liquid for forming the second adhesive layer 5 may be applied onto the first adhesive layer 4 and dried to provide the second adhesive layer 5 on the first adhesive layer 4.
[0135] Step (C) may be carried out substantially simultaneously with step (B). Examples of the coating method for simultaneously forming the first adhesive layer 4 and the second adhesive layer 5 include a sequential coating method and a multi-layer coating method.
[0136] The adhesive film described above may also have a substrate (second substrate) on the surface of the second adhesive layer side (opposite side to the first adhesive layer). The second substrate may be a support film, a protective film, etc., but is preferably a backgrind tape. In this specification, a laminate comprising an adhesive film for a semiconductor and a backgrind tape provided on the side of the adhesive film for a semiconductor opposite to the substrate is referred to as an adhesive tape for a semiconductor.
[0137] The backgrind tape is usually configured so that one of the main surfaces is an adhesive layer. In the adhesive tape for semiconductor of this embodiment, the backgrind tape is provided on the film-like adhesive so that the surface on the adhesive layer side is the film-like adhesive side (for example, so that the adhesive layer and the film-like adhesive are in contact). The thickness of the substrate (for example, the thickness of the backgrind tape) may be 20 to 300 μm.
[0138] The method for producing the adhesive tape is not particularly limited, but since applying and drying a coating liquid onto the adhesive layer of the backgrind tape may result in problems such as destruction of the adhesive layer and migration of components between the adhesive and the adhesive, it is preferable to obtain the adhesive tape by attaching the backgrind tape to a film-like adhesive.
[0139] <Semiconductor device> Another embodiment of the present disclosure is a semiconductor device comprising a semiconductor chip and a base arranged such that their connection portions face each other, and a sealing portion that joins the semiconductor chip and the base and fills a gap between the semiconductor chip and the base, wherein the sealing portion is a cured product of the film-like adhesive in the adhesive film for semiconductor of the above embodiment.
[0140] FIG. 2 is a schematic cross-sectional view showing one embodiment of a semiconductor device. The semiconductor device 100 shown in FIG. 2(a) has a semiconductor chip 20 and a base 25 facing each other, wiring (first connection part and second connection part) 15 arranged on the surfaces facing each other of the semiconductor chip 20 and the base 25, connection bumps 30 connecting the wiring 15 of the semiconductor chip 20 and the base 25 to each other, and a sealing part 40 made of a hardened product of adhesive (first adhesive and second adhesive) filling the gap between the semiconductor chip 20 and the base 25. The semiconductor chip 20 and the base 25 are flip-chip connected by the wiring 15 and the connection bumps 30. The wiring 15 and the connection bumps 30 are sealed by the hardened product of the adhesive and are isolated from the external environment. The sealing part 40 has an upper part 40a including the hardened product of the first adhesive and a lower part 40b including the hardened product of the second adhesive.
[0141] The semiconductor device 200 shown in FIG. 2(b) has a semiconductor chip 20 and a base 25 facing each other, bumps (first and second connection parts) 32 arranged on the facing surfaces of the semiconductor chip 20 and the base 25, respectively, and a sealing part 40 made of a hardened adhesive (first and second adhesive) that fills the gap between the semiconductor chip 20 and the base 25. The semiconductor chip 20 and the base 25 are flip-chip connected by connecting the facing bumps 32 to each other. The bumps 32 are sealed with the hardened adhesive and are isolated from the external environment. The sealing part 40 has an upper part 40a including the hardened first adhesive and a lower part 40b including the hardened second adhesive.
[0142] The semiconductor chip 20 is not particularly limited, and may be a semiconductor chip made of an elemental semiconductor made of the same type of element, such as silicon or germanium, or a semiconductor chip made of a compound semiconductor, such as gallium arsenide or indium phosphide.
[0143] There are no particular limitations on the base 25 as long as it can be used to mount the semiconductor chip 20, and examples thereof include a semiconductor chip, a semiconductor wafer, and a wiring circuit board.
[0144] Examples of the semiconductor chip that can be used as the base 25 are the same as the examples of the semiconductor chip 20 described above, and the same semiconductor chip as the semiconductor chip 20 may be used as the base 25.
[0145] The semiconductor wafer that can be used as the base 25 is not particularly limited, and may be one having a configuration in which a plurality of semiconductor chips such as the semiconductor chip 20 described above are connected together.
[0146] The wired circuit board that can be used as the base 25 is not particularly limited, and examples that can be used include a circuit board having wiring (wiring pattern) 15 formed by etching away unnecessary parts of a metal film on the surface of an insulating substrate whose main component is glass epoxy, polyimide, polyester, ceramic, epoxy, bismaleimide triazine, etc., a circuit board in which wiring 15 is formed on the surface of the insulating substrate by metal plating or the like, and a circuit board in which wiring 15 is formed by printing a conductive material on the surface of the insulating substrate.
[0147] The connection parts such as wiring 15 and bumps 32 contain as their main components gold, silver, copper, solder (the main components being, for example, tin-silver, tin-lead, tin-bismuth, tin-copper, tin-silver-copper, etc.), nickel, tin, lead, etc., and may contain multiple metals.
[0148] Among the above metals, from the viewpoint of obtaining a package having excellent electrical and thermal conductivity at the connection portion, gold, silver and copper are preferred, and silver and copper are more preferred. From the viewpoint of obtaining a package at reduced cost, inexpensive materials such as silver, copper and solder are preferred, copper and solder are more preferred, and solder is even more preferred. Since the formation of an oxide film on the surface of a metal at room temperature can reduce productivity and increase costs, from the viewpoint of suppressing the formation of an oxide film, gold, silver, copper and solder are preferred, gold, silver and solder are more preferred, and gold and silver are even more preferred.
[0149] A metal layer mainly composed of gold, silver, copper, solder (main components are, for example, tin-silver, tin-lead, tin-bismuth, tin-copper, etc.), tin, nickel, etc. may be formed, for example, by plating, on the surfaces of the wiring 15 and bumps 32. This metal layer may be composed of only a single component, or may be composed of multiple components. The metal layer may have a structure in which a single layer or multiple metal layers are laminated.
[0150] The semiconductor device may be a stack of a plurality of structures (packages) such as those shown in the semiconductor devices 100 and 200. In this case, the semiconductor devices 100 and 200 may be electrically connected to each other by bumps, wiring, or the like containing gold, silver, copper, solder (whose main component is, for example, tin-silver, tin-lead, tin-bismuth, tin-copper, tin-silver-copper, etc.), tin, nickel, or the like.
[0151] As a method for stacking a plurality of semiconductor devices, for example, TSV (Through-Silicon Via) technology can be mentioned as shown in FIG. 3. In the semiconductor device 500 shown in FIG. 3, the wiring 15 formed on the interposer 50 is connected to the wiring 15 of the semiconductor chip 20 via the connection bump 30, so that the semiconductor chip 20 and the interposer 50 are flip-chip connected. The gap between the semiconductor chip 20 and the interposer 50 is filled with a hardened product of adhesive (first adhesive and second adhesive), forming a sealing part 40. On the surface of the semiconductor chip 20 opposite to the interposer 50, the semiconductor chips 20 are repeatedly stacked via the wiring 15, the connection bump 30 and the sealing part 40. The wiring 15 on the pattern surfaces on the front and back of the semiconductor chip 20 are connected to each other by the through electrodes 34 filled in the holes penetrating the inside of the semiconductor chip 20. The material of the through electrodes 34 can be copper, aluminum, or the like.
[0152] Such TSV technology makes it possible to obtain signals from the back surface of the semiconductor chip, which is not normally used. Furthermore, since the through electrodes 34 are vertically passed through the semiconductor chip 20, the distance between the opposing semiconductor chips 20 and between the semiconductor chip 20 and the interposer 50 can be shortened, enabling flexible connection. The film-like adhesive for semiconductors of this embodiment can be applied as a film-like adhesive for semiconductors between the opposing semiconductor chips 20 and between the semiconductor chip 20 and the interposer 50 in such TSV technology.
[0153] Furthermore, in a highly flexible bump formation method such as area bump chip technology, a semiconductor chip can be directly mounted on a motherboard without an interposer. The film-like adhesive for semiconductors of this embodiment can also be applied to such cases where a semiconductor chip is directly mounted on a motherboard. The film-like adhesive for semiconductors of this embodiment can also be applied to sealing the gap (void) between two wiring circuit boards when stacking the boards.
[0154] <Method of Manufacturing Semiconductor Device> Another embodiment of the present disclosure is a method for manufacturing a semiconductor device using the adhesive film for a semiconductor of the above embodiment, comprising the step of heating and bonding a semiconductor chip and a base body in a state in which the connection portions of the semiconductor chip and base body are arranged so as to face each other via the film-like adhesive of the adhesive film for a semiconductor of the above embodiment.
[0155] When the adhesive film has a layer having photocuring and thermosetting properties as the first adhesive layer, and a layer having no photocuring properties but has thermosetting properties as the second adhesive layer, the manufacturing method of the semiconductor device may include a light irradiation step of irradiating the first adhesive layer of the film-like adhesive in the adhesive film with light, and a step of heating and bonding the semiconductor chip and the base in a state in which the connection parts of the semiconductor chip and the base are arranged so as to face each other via the film-like adhesive for semiconductors after light irradiation. The light irradiation step is performed in a state in which the film-like adhesive is attached to the connection surface of the semiconductor chip or its precursor, or the connection surface of the base or its precursor from the first adhesive layer side. Here, the precursor of the semiconductor chip means a member that will become a semiconductor chip by processing. A specific example of the precursor of the semiconductor chip is a semiconductor wafer. The same applies to the precursor of the base.
[0156] The method for manufacturing a semiconductor device may further include a step of preparing an adhesive tape comprising a film-like adhesive for semiconductors and a backgrind tape provided on the film-like adhesive for semiconductors on the side opposite to the first adhesive layer side as viewed from the second adhesive layer, a lamination step of attaching the adhesive tape to the connecting surface of a precursor of a semiconductor chip or a precursor of a base from the film-like adhesive side for semiconductors, and a backgrinding step of grinding the precursor to which the adhesive tape is attached from the side opposite to the adhesive tape. The light irradiation in the light irradiation step may be performed through the backgrind tape, but is preferably performed after removing the backgrind tape after the backgrinding step.
[0157] Hereinafter, one embodiment of the method for manufacturing a semiconductor device will be described, taking as an example a mode in which a semiconductor wafer is used as a precursor of a semiconductor chip.
[0158] 4 to 9 are cross-sectional views illustrating steps of a method for manufacturing a semiconductor device according to an embodiment of the present invention. The method for manufacturing a semiconductor device according to an embodiment of the present invention includes the following steps (a) to (e). Step (a): A step of preparing a laminate 9 including a semiconductor wafer 8 having a connection portion (first connection portion) 8a on one main surface (connection surface) and a film-like adhesive 3 provided on the main surface of the semiconductor wafer 8 such that the surface on the first adhesive layer 4 side faces the semiconductor wafer 8 (see FIG. 4). Step (b): A back-grinding step of grinding the side of the laminate 9 opposite to the side where the film-like adhesive 3 is provided (the side opposite to the side where the connection portion 8a of the semiconductor wafer 8 is provided) (see FIG. 5). Step (c): A step of irradiating the laminate 9 after step (b) with light so that the first adhesive layer 4 of the film-like adhesive 3 is irradiated with light (see FIG. 6). Step (d): A step of dividing the laminate 9 after step (b) into individual pieces to obtain semiconductor chips 11 with a film-like adhesive having connection portions 8a (see FIG. 7). Step (e): A step of picking up the semiconductor chip 11 with the film-like adhesive from the side of the individualized film-like adhesive 3a (see FIG. 8). Step (f): A step of electrically connecting the connection portion 8a of the semiconductor chip 11 with the film-like adhesive to the connection portion 12a of the base 12 by placing the semiconductor chip 11 with the film-like adhesive on one main surface (connection surface) of the base 12 from the side of the film-like adhesive 3a and heating the semiconductor chip 11 with the film-like adhesive and the connection portion 12a of the base 12 (see FIG. 9). When a semiconductor wafer whose thickness has been adjusted in advance is used, step (b) does not have to be performed. Step (c) may be performed before step (f), and may be performed before step (b) or after step (d).
[0159] (Step (a)) Step (a) may be a step of preparing a laminate 9 that has been produced in advance, or a step of producing the laminate 9. The laminate 9 may be produced, for example, by the following method.
[0160] First, an adhesive tape 7 having a second substrate 6 provided on the second adhesive layer 5 side of the film-like adhesive 3 is prepared, and this is placed in a predetermined device (see FIG. 4(a)). The second substrate 6 is, for example, a backgrind tape. Next, a semiconductor wafer 8 having a connection portion 8a (wiring, bumps, etc.) on one main surface is prepared, the substrate (first substrate) 2 is peeled off, and the film-like adhesive 3 is attached to the main surface (the surface on which the connection portion 8a is provided, the connection surface) of the semiconductor wafer 8. This results in a laminate 9 in which the semiconductor wafer 8, the first adhesive layer 4, and the second adhesive layer 5 are laminated in this order (see FIG. 4(b)).
[0161] The film-like adhesive 3 can be applied by hot pressing, roll lamination, vacuum lamination, etc. The supply area and thickness of the film-like adhesive 3 are appropriately set depending on the size of the semiconductor wafer and the base, the height of the connection part, etc. In Fig. 4, the thickness of the film-like adhesive 3 is greater than the height of the connection part 8a of the semiconductor wafer 8, and the connection part 8a is covered by the film-like adhesive 3, but the thickness of the film-like adhesive 3 may be less than the height of the connection part 8a.
[0162] (Step (b)) In step (b), the semiconductor wafer 8 of the laminate 9 is ground using, for example, a grinder G (see Figs. 5(a) and 5(b)). This thins the semiconductor wafer 8. The thickness of the semiconductor wafer after grinding may be, for example, 10 µm to 300 µm. From the viewpoint of miniaturizing and thinning the semiconductor device, it is preferable that the thickness of the semiconductor wafer is 20 µm to 100 µm.
[0163] (Process (c)) In step (c), the laminate 9 is irradiated with light to photocure the first adhesive layer 4 (see Figs. 6(a) and 6(b)). In Fig. 6(b), the first adhesive layer after photocure is indicated by the symbol "4'". The light irradiation can be performed, for example, by irradiating light having a wavelength of 150 to 750 nm (e.g., ultraviolet light) from a light source L arranged on the side of the film-like adhesive 3. As the light source L, for example, a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, a metal halide lamp, an LED light source, or the like can be used. The amount of light irradiation can be appropriately adjusted, and for example, the integrated light amount of light having a wavelength of 365 nm can be 100 mJ / cm. 2 or more, and 2 or more, 300 mJ / cm 2 The amount of light irradiation may be, for example, 1000 mJ / cm2 in terms of the integrated light amount of light with a wavelength of 365 nm. 2 or less than 700 mJ / cm 2 may be less than or equal to 500 mJ / cm 2 or less. When the second substrate 6 is transparent, the second substrate 6 may be irradiated with light while it is attached to the laminate 9 as shown in Fig. 6, or the second substrate 6 may be peeled off before the light irradiation. When the second substrate 6 is made of a material that can be peeled off by light irradiation, the step (c) may also serve as a step for peeling off the second substrate 6.
[0164] (Step (d)) In step (d), for example, first, a dicing tape 10 is attached to the semiconductor wafer 8 side of the laminate 9, and the laminate is placed in a predetermined device (see FIG. 7(a)). When step (c) is performed in a state in which the second base material 6 is attached to the laminate 9, the second base material 6 may be peeled off before or after the laminate 9 is attached to the dicing tape 10. Next, the laminate 9 is diced with a dicing saw D. In this way, the laminate 9 is divided into individual pieces, and a semiconductor chip 11 with a film-like adhesive having a film-like adhesive 3a on the semiconductor chip 8' is obtained (see FIG. 7(b)). A connection portion 8a is provided on the surface of the semiconductor chip 8' on the film-like adhesive 3a side. The film-like adhesive 3a has a first adhesive layer (a layer made of a photocured product of the first adhesive) 4a after photocuring and a second adhesive layer (a layer made of the second adhesive) 5a.
[0165] (Step (e)) In step (e), for example, the dicing tape 10 is expanded to separate the semiconductor chips 11 with the film-like adhesive obtained by the above dicing, and the semiconductor chips 11 with the film-like adhesive pushed up by the needles N from the dicing tape 10 side are picked up by a pickup tool P from the film-like adhesive 3a side (see FIG. 8). The picked-up semiconductor chips 11 with the film-like adhesive are transferred to a bonding tool and used for bonding in step (f).
[0166] (Step (f)) In step (f), for example, first, a base 12 for mounting a semiconductor chip having a connection portion 12a (second connection portion) on one side is prepared, and the semiconductor chip 11 with the film-like adhesive and the base 12 are aligned. Next, the semiconductor chip 11 with the film-like adhesive is placed on the main surface of the base 12 on which the connection portion 12a (wiring, bumps, etc.) is provided from the film-like adhesive 3a side using a bonding tool, and heated to bond the semiconductor chip 11 with the film-like adhesive and the base 12 (see Fig. 9(a) and Fig. 9(b)). As a result, the connection portion 8a of the semiconductor chip 11 with the film-like adhesive and the connection portion 12a of the base 12 are electrically connected, and a sealing portion 3a' made of a cured product of the film-like adhesive 3a is formed between the semiconductor chip 8' and the base 12, and the connection portion 8a and the connection portion 12a are sealed, thereby obtaining a semiconductor device 14 which is a bonded body of the semiconductor chip 11 with the film-like adhesive and the base 12. The sealing portion 3a' has an upper portion 4a' containing the cured product of the first adhesive, and a lower portion 5a' containing the cured product of the second adhesive.
[0167] When a solder bump is used for one of the connection portions 8a and 12a (for example, when the connection portion 8a or the connection portion 12a is a wiring provided with a solder bump), the connection portion 8a and the connection portion 12a are electrically and mechanically connected by being soldered.
[0168] The heating in step (f) may be performed while arranging the semiconductor chip, or after arranging the semiconductor chip. The heating and arranging in step (f) may be thermocompression bonding. Step (f) may include a step of temporarily fixing after alignment (temporary fixing step), and a step of melting bumps (e.g. solder bumps) provided on the connection parts by heat treatment to bond the semiconductor chip 8' and the base 12 and seal the connection parts (sealing step). Since it is not necessarily required to form a metal bond at the stage of temporary fixing, the temporary fixing step can be performed with a low load, in a short time, and at a low temperature. Therefore, when the temporary fixing step and the sealing step are performed in step (f), productivity is improved and deterioration of the connection parts can be suppressed.
[0169] The load applied for temporary fixation is appropriately set in consideration of the number of connection parts (bumps), absorbing the variation in height of the connection parts (bumps), controlling the deformation amount of the connection parts (bumps), etc. From the viewpoint of eliminating voids and making it easier to contact the connection parts, the larger the load, the more preferable it is. For example, the load is preferably 0.009 N to 0.2 N per connection part (e.g., bump).
[0170] Heating in the sealing step may be performed using an apparatus capable of heating to a temperature equal to or higher than the melting point of the metal of the connection portion. The heating temperature is preferably a temperature at which the film-like adhesive begins to harden, and more preferably a temperature at which the film-like adhesive is completely hardened. The heating temperature and heating time are appropriately set.
[0171] The heating time in the sealing step varies depending on the type of metal constituting the connection, but from the viewpoint of improving productivity, the shorter the heating time, the better. When solder bumps are used for the connection, the heating time is preferably 20 seconds or less, more preferably 10 seconds or less, and even more preferably 5 seconds or less. In the case of copper-copper or copper-gold metal connection, the connection time is preferably 60 seconds or less.
[0172] In the sealing step, heating and pressure may be applied using a device capable of heating and pressure application. That is, the heating in the sealing step may be heating by thermocompression. In this case, the load (connection load) is set in consideration of the size of the connection member, the number of connection parts, the variation in height, the deformation amount of the connection parts due to pressure, and the like. The connection load may be, for example, 1 MPa or less exceeding atmospheric pressure. From the viewpoint of suppressing voids and improving connectivity, the higher the load, the more preferable, and from the viewpoint of suppressing fillets, the lower the load, the more preferable. From these viewpoints, the load is preferably 0.05 to 0.5 MPa. The pressure bonding time (connection time) varies depending on the type of metal constituting the connection parts, but from the viewpoint of improving productivity, the shorter the time, the more preferable. When the connection parts are solder bumps, the pressure bonding time is preferably 20 seconds or less, more preferably 10 seconds or less, and even more preferably 5 seconds or less. In addition, since direct pressure application using a pressure bonding machine makes it difficult for the heat of the pressure bonding machine to be transmitted to the fillets, pressure application by air pressure is preferable from the viewpoint of easily achieving a sufficient effect on the fillets. From the viewpoint of sealing all at once and suppressing fillets, it is preferable that the pressure during heating be applied by atmospheric pressure (pressure using a pressurized reflow furnace, a pressurized oven, or the like).
[0173] After the semiconductor chip 8' and the base 12 are connected, a heat treatment may be carried out in an oven or the like to further increase the connection reliability. EXAMPLES
[0174] The contents of the present disclosure will be described in more detail below using examples and comparative examples, but the present disclosure is not limited to the following examples.
[0175] <Material preparation> The following materials were prepared and used in the examples.
[0176] (liquid epoxy resin) YX7110B80: Bisphenol F type liquid epoxy, manufactured by Mitsubishi Chemical Corporation. Product name "jER YX7110B80" and "jER" are registered trademarks (hereinafter the same). YL983U: Bisphenol F type liquid epoxy, manufactured by Mitsubishi Chemical Corporation, product name "jER YL983U"
[0177] (Solid epoxy resin) EP1032: Triphenolmethane skeleton-containing multifunctional solid epoxy, manufactured by Mitsubishi Chemical Corporation, product name "jER1032H60"
[0178] (Imidazole-based hardener) 2MAOK-PW: 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, manufactured by Shikoku Chemical Industry Co., Ltd., trade name
[0179] (Phenoxy resin) ZX-1356-2: Phenoxy resin, Tohto Kasei Co., Ltd., product name, Tg = approx. 71°C, weight average molecular weight Mw = approx. 63,000
[0180] (Acrylic Compounds) A-DPH: Dipentaerythritol polyacrylate, product name, manufactured by Shin-Nakamura Chemical Co., Ltd.
[0181] (Photopolymerization initiator) Omnirad 127: 2-hydroxy-1-(4-(4-(2-hydroxy-2-methylpropionyl)benzyl)phenyl)-2-methylpropan-1-one, manufactured by IGM RESINS BV, trade name
[0182] (Organic filler) EXL-2655: Core-shell type organic particles, manufactured by Rohm and Haas Japan Co., Ltd., product name
[0183] (Inorganic filler) KE180G-HLA: Methacrylic surface-treated nano-silica filler, average particle size: approx. 180 nm, manufactured by Admatechs Co., Ltd., product name
[0184] (base material) Substrates 1 to 5: Polyethylene terephthalate (PET) films having the physical properties shown in Table 1 below, which have been surface-treated with a release agent (release treatment).
[0185] [Table 1]
[0186] The contact angle with water and the contact angle with CH2I2 (diiodomethane) in Table 1 refer to the contact angle between the surface of the substrate (PET film) and the surface of a water droplet, and the contact angle between the surface of the substrate and the surface of a CH2I2 droplet. The contact angle was measured using a contact angle meter (DM501, manufactured by Kyowa Interface Science Co., Ltd.). Specifically, 2.0 μL of a probe solution (water or CH2I2) was dropped onto the release-treated surface of the substrate, and the contact angle was measured 1 second after the drop. The measurement was performed 10 times at 20°C, and the average value of the 10 times is shown in the table.
[0187] The surface free energy in Table 1 is the sum of the polar component value and the dispersive component value of the surface free energy, and was calculated by the Owens and Wendt method using the contact angles with water and CH2I2 and the Young-Dupre formula (III).
[0188] The arithmetic mean roughness Ra in Table 1 is the arithmetic mean roughness of the release-treated surface of the substrate (PET film), and was measured using the following measuring device and set conditions. Measuring device: SURFCOM NEX (Tokyo Seimitsu Co., Ltd.) Pickup for roughness measurement: E-DT-SS01A Measurement standards: Compliant with JIS B0601:2013 Stylus shape: 2μmR / 60°cone Cutoff λc: 0.25mm Cutoff λs ratio: 300 Filter: Gaussian Measurement length: 1.25mm Measurement speed: 0.3mm / s Measurement load: 750μN -Remove shapes with least squares straight line
[0189] The tape peeling strength in Table 1 was measured by the following method.
[0190] A substrate (PET film) measuring 35 mm x 450 mm was prepared, and a polyester adhesive tape (manufactured by Nitto Denko Corporation, product number: No. 31B, 50 mm width) was applied to the release-treated surface of the substrate by rolling a 1 kg roller back and forth once, and a test piece for measuring peel strength measuring 25 mm x 150 mm width was cut out. At this time, the long side was aligned in the longitudinal direction of the substrate. The peel strength of the obtained test piece was measured 30 minutes after the polyester adhesive tape was applied. An adhesive / coating peel analysis device (product name: VPA-2 (load cell 100 N)) manufactured by Kyowa Interface Co., Ltd. was used to measure the peel strength. Specifically, the release sheet side of the test piece was fixed to a SUS plate with double-sided tape, and the polyester adhesive tape was bent 180° while peeling a length of 100 mm at a speed of 300 mm / min. Since there may be variation in the measured values up to 10 mm after the start of peeling, the peel force (mN / 25 mm) was calculated using the measured values from a distance of 10 to 100 mm from the start of peeling (a total of 90 mm). Measurements were performed three times for each substrate, and the average value of the three measurements is shown in Table 1.
[0191] <Examples 1 to 4 and Comparative Example 1> (Preparation of coating liquid for forming adhesive layer) Among the components shown in Table 2, the components other than the photopolymerization initiator were added to an organic solvent (methyl ethyl ketone) so that the NV value ([mass of paint after drying] / [mass of paint before drying]×100) was 60%, and a mixed liquid was obtained. At this time, the amount of each component added was the amount shown in Table 2 (unit: parts by mass). Then, Φ1.0 mm beads and Φ2.0 mm beads were added to the above mixed liquid, and the mixture was stirred for 30 minutes with a beads mill (Fritsch Japan Co., Ltd., planetary fine grinder P-7). The amount of beads added was the same mass as the non-volatile content of the mixed liquid (total amount of components other than the organic solvent). After stirring, the beads were removed by filtration. Next, the amount of photopolymerization initiator shown in Table 2 (unit: parts by mass) was added to the obtained mixture, and the mixture was stirred and mixed to obtain a coating liquid for forming an adhesive layer.
[0192] (Measurement of surface free energy of adhesive layer) The coating liquid obtained above was used to form an adhesive layer for measuring surface free energy. Specifically, the coating liquid was applied to the surface of the substrate used in the examples using a small precision coating device (Kanei Seiki) so that the film thickness after drying was 3.4 μm, and the coating film was dried (80° C. / 10 min) in a clean oven (manufactured by ESPEC) to form an adhesive layer on the substrate used in the examples. The obtained adhesive layer was peeled off from the substrate to obtain a sample for measuring surface free energy. Next, the surface free energy (dispersion component value and polar component value) of the surface of the obtained sample that was in contact with the substrate was determined by the same method as in the measurement of the surface free energy of the substrate. Furthermore, the preparation of a sample for measuring surface free energy and the measurement of surface free energy were performed in the same manner except that materials of different lots were used.
[0193] The surface free energy (sum of the dispersion component value and the polar component value) and the polar component value A of the surface free energy measured for the two samples above 極性 The average value of the surface free energy of the surface of the adhesive layer formed using the coating liquid in contact with the substrate and the polar component value A of the surface free energy 極性 The results are shown in Table 2.
[0194] [Table 2]
[0195] <Preparation of adhesive film> The coating solution obtained above was applied to the release-treated surfaces of the substrates 1 to 5 using a small precision coating device (Kanei Seiki) so that the film thickness after drying would be 3.4 μm, and the coating film was dried (80° C. / 10 min) in a clean oven (manufactured by ESPEC). As a result, an adhesive layer was formed on each substrate (substrates 1 to 5), and adhesive films of Examples 1 to 4 and Comparative Example 1 were obtained, respectively.
[0196] <Evaluation> The number of defects (number of defects) in the adhesive layer in the adhesive films of Examples 1 to 4 and Comparative Example 1 was evaluated by the following method. First, the film-like adhesive was peeled off from the adhesive film, and then 10 cm square sheets (total of 3 sheets) were cut out from any 3 positions of the peeled film-like adhesive. Next, each sheet was observed using an optical microscope (Keyence Corporation: VHX-6000) and the number of defects was counted. In this evaluation, circular depressions with diameters of 200 μm to 500 μm were regarded as defects. The average number of defects in each sheet was calculated and evaluated according to the following criteria. The results are shown in Table 3. ×: The average number of defects is 15 or more 〇: The average number of defects is 1 to 14 ◎: 0 defects
[0197] [Table 3] [Explanation of symbols]
[0198] 1...adhesive film for semiconductor, 2...substrate (first substrate), 3...film-like adhesive, 4...adhesive layer (first adhesive layer), 5...adhesive layer (second adhesive layer), 6...backgrind tape (second substrate), 7...adhesive tape, 8...semiconductor wafer, 8a...connection portion (first connection portion), 8'...semiconductor chip, 12...base, 12a...connection portion (second connection portion), 14...semiconductor device, 15...wiring (first connection portion and second connection portion), 20...semiconductor chip, 25...base, 30...connection bump, 32...bump (first connection portion and second connection portion), 40...sealing portion, 100, 200, 500...semiconductor device.
Claims
1. An adhesive film for a semiconductor comprising a substrate and a film-like adhesive in contact with the substrate, the film-like adhesive has an adhesive layer having a thickness of 1 to 10 μm in contact with the base material, The polar component value A of the surface free energy of the surface of the adhesive layer in contact with the substrate 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference with (|A 極性 -B 極性 |) is 8 mJ / m 2 The following is an adhesive film for semiconductors.
2. The adhesive film for a semiconductor according to claim 1 , wherein the adhesive layer contains an epoxy resin, a curing agent, a thermoplastic resin, and an inorganic filler.
3. 3. The adhesive film for a semiconductor according to claim 2, wherein the content of the epoxy resin is 10 to 60 mass % based on the total mass of the adhesive layer.
4. 3. The adhesive film for a semiconductor according to claim 2, wherein the content of the curing agent is 1 to 40 mass % based on the total mass of the adhesive layer.
5. 3. The adhesive film for a semiconductor according to claim 2, wherein the thermoplastic resin comprises at least one selected from the group consisting of polyamideimide resin, acrylic resin, polyimide resin, and phenoxy resin.
6. 3. The adhesive film for a semiconductor according to claim 2, wherein the content of the thermoplastic resin is 5 to 40 mass % based on the total mass of the adhesive layer.
7. 3. The adhesive film for a semiconductor according to claim 2, wherein the content of the inorganic filler is 30 to 60 mass % based on the total mass of the adhesive layer.
8. 2. The adhesive film for a semiconductor according to claim 1, wherein the substrate is a polyethylene terephthalate film.
9. The surface free energy of the surface of the substrate in contact with the adhesive layer is 10 to 30 mJ / m 2 2. The adhesive film for a semiconductor according to claim 1 ,
10. The polar component value B 極性 is 0.3 to 5.0 mJ / m 2 2. The adhesive film for a semiconductor according to claim 1 ,
11. A method for producing an adhesive film for a semiconductor according to any one of claims 1 to 10, A step (A) of preparing the substrate and a coating liquid for forming the adhesive layer; and (B) applying the coating liquid to a surface of the substrate to form the adhesive layer, In the step (A), the polar component value A of the surface free energy of the surface of the adhesive layer that contacts the substrate is 極性 and the polar component value B of the surface free energy of the surface of the substrate in contact with the adhesive layer. 極性 Difference with (|A 極性 -B 極性 |) is 8 mJ / m 2 The method for producing an adhesive film for a semiconductor includes preparing the substrate and the coating liquid as follows.
12. 11. An adhesive tape for a semiconductor comprising: the adhesive film for a semiconductor according to claim 1; and a backgrind tape provided on the side of the adhesive film for a semiconductor opposite to the substrate.
13. A method for producing a semiconductor device using the adhesive film for semiconductor according to any one of claims 1 to 10, A method for manufacturing a semiconductor device, comprising a step of heating and bonding a semiconductor chip and a base body in a state in which the connecting portions of the semiconductor chip and base body face each other via the film-like adhesive.
14. a semiconductor chip and a base body arranged such that their connection portions face each other; and a sealing portion that bonds the semiconductor chip and the base body and fills a gap between the semiconductor chip and the base body, A semiconductor device, wherein the sealing portion is a cured product of the film-like adhesive in the adhesive film for semiconductor use according to any one of claims 1 to 10.
Citation Information
Patent Citations
Film-like adhesive for semiconductors, semiconductor device production method, and semiconductor device
WO2018225323A1